INVENTORY TURNOVER AND WORKING CAPITAL ANALYSIS FOR ASSESSING FINANCIAL PERFORMANCE AT PT. GUDANG GARAM Tbk LISTED ON THE IDX PERIOD 2017 – 2021 - Yand. S, Britny; Ramli, Anwar; Nurman; Akbar, Abdi; Musa, Muh. Ichwan (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the financial performance at PT. Gudang Garam Tbk in the 2017-2021 period in terms of inventory turnover ratio and to find out the financial performance of PT. Gudang Garam Tbk in the 2017-2021 period in terms of the working capital turnover ratio. This research is a quantitative research with a descriptive approach where the subject of this research is PT. Gudang Garam Tbk. Based on the analysis that has been done, it is obtained that the value of the inventory ratio and the ratio of working capital at PT. Gudang Garam experienced fluctuations when the financial performance tested by the liquidity, solvency and profitability ratios was stated to be good, which means that the financial performance remained in good condition.